2008
DOI: 10.1042/bst0360916
|View full text |Cite
|
Sign up to set email alerts
|

The diverse roles of protein kinase C in pancreatic β-cell function

Abstract: Members of the serine/threonine PKC (protein kinase C) family perform diverse functions in multiple cell types. All members of the family are activated in signalling cascades triggered by occupation of cell surface receptors, but the cPKC (conventional PKC) and nPKC (novel PKC) isoforms are also responsive to fatty acid metabolites. PKC isoforms are involved in various aspects of pancreatic beta-cell function, including cell proliferation, differentiation and death, as well as regulation of secretion in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…PKC ␤ was also one of the earliest isoforms recognized in insulin signaling and appears to play dual roles in insulin signaling pathways (17)(18)(19)(20)(21)(22). PKC ␤ does not appear to regulate glucose-induced insulin secretion in vivo ( 23 ), even though it has been reported to undergo translocation to the plasma membrane subsequent to stimulation by glucose in primary islet cells ( 24 ). We recently showed that PKC ␤ is markedly elevated in white adipose tissue (WAT) of leptin-defi cient ( ob/ob ) mice and is signifi cantly induced by intake of high-fat diet (HFD) ( 25,26 ).…”
Section: Western Blot Studiesmentioning
confidence: 99%
“…PKC ␤ was also one of the earliest isoforms recognized in insulin signaling and appears to play dual roles in insulin signaling pathways (17)(18)(19)(20)(21)(22). PKC ␤ does not appear to regulate glucose-induced insulin secretion in vivo ( 23 ), even though it has been reported to undergo translocation to the plasma membrane subsequent to stimulation by glucose in primary islet cells ( 24 ). We recently showed that PKC ␤ is markedly elevated in white adipose tissue (WAT) of leptin-defi cient ( ob/ob ) mice and is signifi cantly induced by intake of high-fat diet (HFD) ( 25,26 ).…”
Section: Western Blot Studiesmentioning
confidence: 99%
“…Rodent studies have shown that chronically elevated glucose downregulates both GLP-1R and GIP-R gene expression in vivo [16,17]. Glucose is also considered likely to activate PKC isoforms in the β-cell [18], which may be the stimulus for PKC-mediated phosphorylation of the GLP-1R that leads to its downregulation [19–21]. Homologous GLP-1R activation has been shown to downregulate the receptor rapidly [21,22], consistent with a classical negative feedback system that may be mediated via cAMP signaling.…”
Section: Introductionmentioning
confidence: 99%
“…PKC proteins regulate cellular granule movement and exocytosis [32][33][34][35][36] that also exists in β cells, constituting the distal stages of GIIS regulation. PKC family proteins, PKCα and PKCε, PKCβII, PKCζ, and PKCδ in this study, were found to exhibit up-regulated protein levels in islets from HFD control mice ( Fig.…”
Section: Mtorc2/pkc Signalling and The Pma-stimulated Insulin Secretimentioning
confidence: 99%